On the central abundances of Active Galactic Nuclei and Star-forming Galaxies - Dors Jr., O. L. (2015)
We examine the relation between oxygen abundances in the narrow-line regions (NLRs) of active galactic nuclei (AGNs) estimated from the optical emission lines through the strong-line method (the theoretical calibration of Storchi-Bergmann et al. 1998), via the direct Te-method, and the central intersect abundances in the host galax- ies determined from the radial abundance gradients. We found that the Te-method underestimates the oxygen abundances by up to ∼2 dex (with average value of ~0.8 dex) compared to the abundances derived through the strong-line method. This con- firms the existence of the so-called ?temperature problem? in AGNs. We also found that the abundances in the centres of galaxies obtained from their spectra trough the strong-line method are close to or slightly lower than the central intersect abun- dances estimated from the radial abundance gradient both in AGNs and Star-forming galaxies. The oxygen abundance of the NLR is usually lower than the maximum at- tainable abundance in galaxies (~2 times the solar value). This suggests that there is no extraordinary chemical enrichment of the NLRs of AGNs.